Anti-de Sitter (AdS) spacetime - Villegas, Fulgencio (2019)
In this work a basic introduction is made about the space-time of Sitter and Anti-Sitter. For the Sitter space, two equivalent metrics are calculated, one using static coordinates and the other using Friedmann- Lemaître-Robertson-Walker coordinates (FLRW). In the case of the Anti-Sitter space, the condition that the cosmological constant must meet is determined to be a solution of Einstein's equations and nally, using global coordinates, its metric is determined.